Do perceived health risks outweigh the benefits of modern contraceptives? A qualitative study in a suburban population in Istanbul, Turkey - TOPUZOĞLU, AHMET; SAVE, DİLŞAD; AY, NADİYE PINAR; HIDIROĞLU, SEYHAN (TAYLOR & FRANCIS LTD, 2007)
Objectives To evaluate the health concerns and the perceived non-contraceptive benefits of modern contraceptive methods through utilizing qualitative methods. Methods Six focus group discussions were carried out with a total of 53 married women in a socio-economically disadvantaged community in Istanbul, Turkey. Results Women had a vague knowledge of the mechanism of menstruation. Some women believed that the uterus was filled with blood-termed 'dirty blood'-which should be eliminated during menstruation in order to stay healthy. For this reason, amenorrhoea was recognized as the important disadvantage of the progestin-only injectable contraceptives. While the participants mentioned fallacious and exaggerated side effects related to modern methods they did not recognize their non-contraceptive benefits. Most women gained the information concerning side effects through their social networks. Sometimes the information acquired was based on rumours that biased women against the modern contraceptives. Conclusions Women outweighed the risks, some of which were fallacious and exaggerated, against the benefits of modern contraceptives. It is crucial to address health concerns of women and what they 'heard' from their peers during counselling sessions. Also the non-contraceptive health benefits of modern methods should be well emphasized. Since informal sources are prevalent, the effectiveness of peer education should be studied in this community.
Keywords: health concerns; side effects; non-contraceptive benefits; contraception; family planning; Turkey; WOMENS PERCEPTIONS; REASONS